Agrowisata Kebun Anggur Sebagai Potensi Unggulan Desa Patalan, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta - Pratama, Yohanes Mario (Jurnal Atma Inovasia, 2022)
Patalan Village, Kapanewon Jetis, Bantul Regency has tourism potential in the form of a vineyard named Jogja Wine. This work program is carried out with the aim that this vineyard will develop into a tourist village and be known by the wider community. This work program focuses on analyzing and designing facilities and tour packages that can invite outsiders to know more about Jogja Wines and even Patalan Village. In addition, it will discuss the development of products from the vineyard which is one of the unique things for Patalan Village. The data collection method was carried out by collecting secondary data after it was arranged systematically. The result of this work program is the addition of facilities in vineyard agro-tourism such as cafes, gazebos, and wine production houses. There is also an explanation regarding the making of grape leaf chips and grape juice. This work program is expected to increase the potential of Patalan Village so that it has an impact on improving the village economy. Maximum achievement of the utilized potential also requires cooperation or support from the village government and village communities who play an important role in developing the potential of Patalan Village.